2017
DOI: 10.1371/journal.pone.0177988
|View full text |Cite|
|
Sign up to set email alerts
|

Sexual dimorphisms of mRNA and miRNA in human/murine heart disease

Abstract: BackgroundSexual dimorphisms are well recognized in various cardiac diseases such as ischemic cardiomyopathy (ICM), hypertrophic cardiomyopathy (HCM) and dilated cardiomyopathy (DCM). Thorough understanding of the underlying genetic programs is crucial to optimize treatment strategies specified for each gender. By performing meta-analysis and microarray analysis, we sought to comprehensively characterize the sexual dimorphisms in the healthy and diseased heart at the level of both mRNA and miRNA transcriptome.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 97 publications
1
21
0
Order By: Relevance
“…Studies analyzing healthy human as well as mouse hearts reported only a modest number of genes (~30–125) that were expressed in a sexually dimorphic manner. 16, 37 However, a previous microarray study in our lab analyzing mouse left ventricles reported sex-specific expression of ~2000 genes with most of the genes being enriched in the male samples 23 . While we detected around 600 genes that were differentially expressed in ARVMs from either sex, we did not observe a difference in the overall number of genes that were more highly expressed in one sex relative to the other (Figure 2B).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies analyzing healthy human as well as mouse hearts reported only a modest number of genes (~30–125) that were expressed in a sexually dimorphic manner. 16, 37 However, a previous microarray study in our lab analyzing mouse left ventricles reported sex-specific expression of ~2000 genes with most of the genes being enriched in the male samples 23 . While we detected around 600 genes that were differentially expressed in ARVMs from either sex, we did not observe a difference in the overall number of genes that were more highly expressed in one sex relative to the other (Figure 2B).…”
Section: Discussionmentioning
confidence: 97%
“…Sexually dimorphic enrichment of pathways such as the immune response and lipid metabolism appear to be strongly conserved among a variety of tissues such as liver, adipose, skeletal muscle, heart as well as in our cardiac myocyte samples (Figure 4). 16, 18, 20, 3537 Previous reports in the heart have observed GeneOntology categories such as metabolism Reviewed in:21 , signaling transduction, regulation of cell growth, size and cell death to be enriched in a sex-specific manner. 16, 20, 23, 37 Our results agree with these reports as Rho and Rac signaling and genes involved in regulating cell growth and death were enriched in male ARVMs, whereas female myocytes were enriched for processes such as energy metabolism and gene expression (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-34a reduces the shortening of telomeres, damage of the DNA response, and myocardial cell apoptosis by targeting protein phosphatase 1 regulatory subunit 10 [2], and miR-10a regulates vessel formation by targeting fms-related tyrosine kinase 1[3]. However, the expression profiles might change during cardiovascular disease (CVD) [4]. For example, miR-29 was decreased after acute myocardial infarction, which targets a cadre of mRNAs encoding proteins involved in fibrosis to promote the fibrotic response [5].…”
Section: Introductionmentioning
confidence: 99%
“…It can be speculated that circ_0126991 also plays a crucial role in the pathogenesis of EH and may be identified as a sponge for miR-10a-5p. Gender differences were detected in the relative expression of miR-497-5p, miR-10a-5p, and circ_0126991, and, including genome and transcriptome, are well-identified in a variety of cardiovascular diseases [InanlooRahatloo et al, 2017;Tsuji et al, 2017]. The latest evidence suggests that there are significant sexual dimorphisms in the mRNA and miRNA transcriptome in normal and disease heart tissues [Tsuji et al, 2017].…”
Section: Discussionmentioning
confidence: 99%
“…Gender differences were detected in the relative expression of miR-497-5p, miR-10a-5p, and circ_0126991, and, including genome and transcriptome, are well-identified in a variety of cardiovascular diseases [InanlooRahatloo et al, 2017;Tsuji et al, 2017]. The latest evidence suggests that there are significant sexual dimorphisms in the mRNA and miRNA transcriptome in normal and disease heart tissues [Tsuji et al, 2017]. Bammert et al [2017] report that miR-125a and miR-34a expression showed significant sexrelated differences in circulating endothelial microparticles, and these vascular-related miRNAs have been linked to endothelial dysfunction and cardiovascular disease risk.…”
Section: Discussionmentioning
confidence: 99%